2022
DOI: 10.1038/s41531-022-00394-9
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L-containing exosomes from α-synuclein-activated microglia induce neurotoxicity through the P2X7 receptor

Abstract: Uncontrolled microglial activation is pivotal to the pathogenesis of Parkinson’s disease (PD), which can secrete Cathepsin L (CTSL) to affect the survival of neurons in the PD patients; however, the precise mechanism has yet to be determined. We demonstrated for the first time that CTSL was mostly released by exosomes derived from α-Syn-activated microglia, resulting in neuronal damage and death. The elevation of CTSL activity was blocked by GW4869, suggesting a critical role for exosomes in mediating CTSL rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Xia et al found that microglia exosomes are involved in the α-Sny aggregation in the pathological process ( 119 ). Activated microglia releases exosomes that promote the infection of insoluble α-Sny with normal cells and propagate the aggregation of pathological α-Sny, which is accelerated by pro-inflammatory factors released in response to microglia inflammation, and the use of GW4869 (an inhibitor of sphingosine phosphodiesterase) significantly reduces the number of exosomes and decreases α -Sny proliferation and aggregation, leading to the possibility of targeting microglia exosomes for PD treatment ( 120 ). Also, age-related changes in the inflammatory response, as well as genetic and environmental factors, may contribute to the prevalence of pro-inflammatory microglia and affect the susceptibility to microglia activation, which may further influence the pathogenesis and lead to progressive neuronal loss.…”
Section: Microglia Activation and Cns Disordersmentioning
confidence: 99%
“…Xia et al found that microglia exosomes are involved in the α-Sny aggregation in the pathological process ( 119 ). Activated microglia releases exosomes that promote the infection of insoluble α-Sny with normal cells and propagate the aggregation of pathological α-Sny, which is accelerated by pro-inflammatory factors released in response to microglia inflammation, and the use of GW4869 (an inhibitor of sphingosine phosphodiesterase) significantly reduces the number of exosomes and decreases α -Sny proliferation and aggregation, leading to the possibility of targeting microglia exosomes for PD treatment ( 120 ). Also, age-related changes in the inflammatory response, as well as genetic and environmental factors, may contribute to the prevalence of pro-inflammatory microglia and affect the susceptibility to microglia activation, which may further influence the pathogenesis and lead to progressive neuronal loss.…”
Section: Microglia Activation and Cns Disordersmentioning
confidence: 99%
“…While this study cannot establish a causal link between microglial activation and α-synuclein-related neurodegeneration, it aligns with preclinical and neuropathological evidence that supports a contributory role in cell death. Microgliosis precedes cell death in α-synuclein over-expression animal models (28) and in human autopsy studies(23) and at least two mechanisms have been proposed: 1) direct or indirect (via activation of neurotoxic astrocytes) toxicity to neurons by α-synuclein-activated microglia (1, 23, 29) and 2) microglia-mediated enhancement of α-synuclein oligomerization(30) and spread throughout the brain(31, 32). Since some of the most promising disease-modifying agents in PD(33) are thought to act via microglia(7), having an in vivo biomarker for microglial activity may facilitate therapy development and hasten drug trials as an indicator of target engagement in proof-of-principle studies and clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the activation of P2X7R in microglia triggers inflammatory intracellular signaling via the PI3K/Akt signaling and NF-κB signaling pathways, 26,27 combined with RNA-seq data. We used qRT-PCR and WB analysis to confirm these pathways.…”
Section: Upregulating Lnctcons_00058568 Inhibited Pi3k/akt and Nf-κb ...mentioning
confidence: 99%